Distribución, abundancia, densidad y morfometría de Strombus gigas (Mesogasteropoda: Strombidae) en el Arrecife Alacranes, Yucatán, México - Pérez Pérez, Manuel (2000)
A population of the conch Strombus gigas was sampled in 109 transects (100X10 m each) for an area of 109 000 m2 (eight surveys in 1998 and six in 1999) in Yucatan, Mexico; S. gigas was the most abundant conch species (97% of individuals)and ocurred at depths of 0.5-18 m. Mean density was 0.0084 individuals/m2 (Standard deviation SD=0.0138, n=1910). Maximum density (0.015 individuals/m2) was at 0.5-2 m and minimal (0.001 individuos/m2) at 16-18 m. Shell length was120-290 mm (mena=211.6, SD=26, n=1136). Shell lip thickness, measured only in adults, was 1-28 mm (mean=8.7, SD=7.5, n=1136).